ANALISIS PENGARUH KINERJA KEUANGAN, MANAJEMEN RISIKO DAN MANAJEMEN MODAL KERJA TERHADAP RETURN SAHAM - Dwian Wahyu Prabawa; Fitri Lukiastuti (Jurnal Manajemen Indonesia, 2015)
Level stock returns telecommunications in Indonesia is influenced by various factors such as financial performance, risk management and working capital management. The purpose of this research was to analyze the influence of financial performance through parameters Debt to Equity Ratio (DER), Return On Investment (ROI), Current Ratio (CR) dan Total Assets Turn Over (TATO). Risk management using parameters (interest rate) and working capital management using parameters Cash Conversion Cycle (CCC). The population in this study is a telecommunications companies listed in Indonesia Stock Exchange 2010-2013. In analyzing the effect of variable DER, ROI, CR, TATO, ir and CCC using multiple linear regression. The analysis showed that the Debt to Equity Ratio (DER) has effect on stock returns with significant value 0,009, Return on Investment (ROI) has effect on stock returns with significant value 0,006. And Total Asset Turn Over (TATO) has effect on stock returns with significant value 0,025. While the Current Ratio (CR) ,interest rate, and Cash Conversion Cycle not effect on stock returns with significant value 0,403; 0,047; 0,977. All the independent variables simultaneously affect the stock on telecommunication companies.